Adolescent Girls in Malawi : Introduction and Overview - World Bank Group (World Bank, Washington, DC, 2016)
Adolescence is a time of transitions that foster both challenges and opportunities. Indeed, choices made during adolescence not only have immediate consequences but also greatly influence the economic opportunities, health outcomes, and skill sets attained later in life, and yet it is the same period when social norms create pathways largely defined by gender. Poverty and ethnic minority status can further magnify gender discrepancies for youth worldwide, as reductions in household spending on education, health care, and nutrition are often more likely to affect adolescent girls than boys. In Malawi, adolescents make up 24% of the total population, a substantial proportion that is expected to become higher than neighboring countries if current trends continue. The high prevalence of child marriage and teenage pregnancy among Malawian girls greatly contributes to the high fertility and population growth trends, and is also closely interrelated with a range of economic and socio-cultural determinants that perpetuate a vicious cycle for the poorest and most vulnerable girls and have costly consequences for them and for the nation as a whole. In order to initiate the potential for a demographic dividend, Malawi will need to initiate a demographic transition. Reducing child marriage and teenage pregnancy can significantly contribute to the fertility declines needed to accelerate this demographic transition and would lead to better life outcomes for adolescent girls and better opportunities for the next generation. Accordingly, this series of policy briefs focuses on four key areas of interventions (or pillars) as follows: (i) maintaining girls in school; (ii) equipping out-of-school girls with skills; and (iii) beginning a family and supporting girls to adopt healthy lifestyles; and (iv) addressing the child development needs of children born to teenage mothers.